A new tetraphenylethylene based AIE sensor with light-up and tunable measuring range for adenosine triphosphate in aqueous solution and in living cells. Issue 23 (8th November 2017) - Jiang, Guoyu; Zhu, Wenping; Chen, Qingqing; Shi, Aiping; Wu, Yongquan; Zhang, Guanxin; Li, Xun; Li, Yongdong; Fan, Xiaolin; Wang, Jianguo
Abstract : An AIE probe, TPPTPE, was synthesized with light-up sensing and tunable measuring range for adenosine triphosphate in aqueous solution and in living cells. Abstract : An AIE based tetraphenylethylene derivative (TPPTPE) was synthesized for light-up sensing of ATP in aqueous solution. The measuring range for ATP can be tuned by varying the concentration of the TPPTPE. A one-step straightforward quantitative analysis of the ATP level in cell lysates can be realized using the TPPTPE. Moreover, the TPPTPE can be used for monitoring apyrase activity in aqueous solution and detecting ATP both in living cancer cell lines and in living normal cell lines.